How stable is the internet to malign or economic interference? - Fredrik Lindeberg (International Telecommunications Society (ITS), 2017)
This text is a working paper on the social resilience of the Internet, which means who can change how we do end-to-end best effort digital communication and how can they change it. I assume a bottom up organized version of the Internet and focus on the Internet itself. The texts goes through varying factors capable of through social means changing what the Internet is through intention or error, and concludes that a changing world order has the greatest impact on what the Internet will be in the future.
Keywords: 330